1999
DOI: 10.1111/j.1600-0447.1999.tb05992.x
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing fronto‐striatal circuitry and neuroleptic effects in schizophrenia

Abstract: Disturbances in fronto‐striatal circuitry have been postulated to be important in schizophrenia. Positron emission tomography typically shows decreased metabolic rates in these areas relative to other brain areas in schizophrenia. After treatment with typical neuroleptics, striatal metabolic rates are increased, but other brain areas tend not to show significant changes. Atypical neuroleptics less markedly affect striatal metabolic rates, but show wider cortical effects. In order to examine fronto‐striatal cir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2002
2002
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 53 publications
0
11
0
1
Order By: Relevance
“…FDG PET studies have confirmed lower metabolic rates in all three areas (57), and studies of N-acetyl-D-aspartic acid concentrations have demonstrated lower metabolic rates in frontal and striatal areas (58). Since the centromedian nucleus sends an excitatory projection to the striatum (18), diminished centromedian nucleus activity would be consistent with the lower levels of striatal and cortical activation seen in patients with schizophrenia, compared to healthy subjects.…”
Section: Striatum-thalamus Interactions and Centromedian Nucleusmentioning
confidence: 80%
“…FDG PET studies have confirmed lower metabolic rates in all three areas (57), and studies of N-acetyl-D-aspartic acid concentrations have demonstrated lower metabolic rates in frontal and striatal areas (58). Since the centromedian nucleus sends an excitatory projection to the striatum (18), diminished centromedian nucleus activity would be consistent with the lower levels of striatal and cortical activation seen in patients with schizophrenia, compared to healthy subjects.…”
Section: Striatum-thalamus Interactions and Centromedian Nucleusmentioning
confidence: 80%
“…Stimulants, however, were withheld for 24 to 48 hours before fMRI to minimize their behavioral and cerebral effects. There have been reports of increased caudate activity 83 and decreased ACC activity 84 associated with antipsychotic medications as well as decreased ventral ACC activity associated with antidepressants. 81,85 Although betweengroup caudate differences may have been related to this phenomenon, it is unlikely to explain the findings of increased ACC activity in subjects with BD.…”
Section: Limitations and Strengthsmentioning
confidence: 99%
“…that may dominate interregional covariances, and which should be a concern with any examination of this kind. In this regard, several studies have examined interregional covariance in major depression (Mallet et al, 1998; Anand et al, 2005), schizophrenia (Clark et al, 1984; Katz et al, 1996; Friston et al, 1996; Buchsbaum et al, 1999; Mallet et al, 1998; Andreason, 1999; Meyer-Lindenberg et al, 2001), obsessive-compulsive disorder (Horwitz et al, 1991b; Mallet et al, 1998), and Down’s syndrome (Horwitz et al, 1990). …”
Section: Introductionmentioning
confidence: 99%